2020
DOI: 10.1038/s41598-020-72702-3
|View full text |Cite
|
Sign up to set email alerts
|

Crawl positioning improves set-up precision and patient comfort in prone whole breast irradiation

Abstract: Prone positioning for whole-breast irradiation (WBI) reduces dose to organs at risk, but reduces set-up speed, precision, and comfort. We aimed to improve these problems by placing patients in prone crawl position on a newly developed crawl couch (CrC). A group of 10 right-sided breast cancer patients requiring WBI were randomized in this cross-over trial, comparing the CrC to a standard prone breastboard (BB). Laterolateral (LL), craniocaudal (CC) and anterioposterior (AP) set-up errors were evaluated with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…Shen et al [20] designed a new breast vacuum bag to obtain the M PTV boundary values of 0.44 cm, 0.31 cm, and 0.38 cm required for X, Y, and Z, respectively, which were smaller than those obtained in this study. Deseyne et al [21] used a modified prone breastplate to obtain the M PTV boundary values of 1.14 cm, 1.21 cm, and 1.0 cm required for X, Y, and Z, respectively, which were greater than those obtained in this study. Cravo Sá A et al [22] employed 3D surface image guidance to achieve the expanded M PTV boundary values of 0.89 cm, 10.4 cm, and 0.93 cm required for X, Y, and Z, respectively, which were greater than the values in the usual weather group and similar to those in the cold weather group in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…Shen et al [20] designed a new breast vacuum bag to obtain the M PTV boundary values of 0.44 cm, 0.31 cm, and 0.38 cm required for X, Y, and Z, respectively, which were smaller than those obtained in this study. Deseyne et al [21] used a modified prone breastplate to obtain the M PTV boundary values of 1.14 cm, 1.21 cm, and 1.0 cm required for X, Y, and Z, respectively, which were greater than those obtained in this study. Cravo Sá A et al [22] employed 3D surface image guidance to achieve the expanded M PTV boundary values of 0.89 cm, 10.4 cm, and 0.93 cm required for X, Y, and Z, respectively, which were greater than the values in the usual weather group and similar to those in the cold weather group in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…For prone positioning, there is a problem about postural repeatability. Although Deseyne et al 42 demonstrated that a newly developed crawl couch could improve precision and comfort and reduce set-up errors compared to the standard prone breast board in prone-WBI. Lakosi et al 43 analyzed respiratory motion of surgical clips, chest wall (CW) and the anterior displacement of the heart, results showed that prone position significantly reduced respiration related CW and surgical clip movements but increased anterior heart displacement.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of prone radiotherapy is simple—in prone setup, the breast hangs down from the chest wall through an aperture on the support couch, facilitating avoidance of intrathoracic organs with radiation tangential fields—but the implementation is not. It requires the full radiation team to collaborate on many levels, to address the challenges of implementing prone setup that include, among other: comfort of the patient (53.4% preferred supine, Table 1 ), stability and set-up precision using the present prone devices, the need for new devices 24 , the longer set-up times. Surface-guided set-up systems reported for supine 25 are not well suited for prone breast positioning.…”
Section: Discussionmentioning
confidence: 99%